Examine the perception on the integration of building information modelling and artificial intelligence in construction projects - Lee, Jie Anne (2021)
Building Information Modelling (BIM) is becoming a growing data respiratory for the whole project lifecycle. However, the is an absence of approaches to utilise this data and generate value for the construction industry. Artificial Intelligence (AI) has the potential to harness this data gathered in the BIM models to aid in the development of BIM and automate BIM processes. Nonetheless, the potentials of integrating these two technologies have only been briefly mentioned in existing studies and the perception of the probable users of this technology are not demystified. What breakthroughs can this integration achieve for BIM? Do construction practitioners think these breakthroughs are beneficial to them? Are they willing to use these advanced BIM applications in the future and if not, what is obstructing them from doing so? This study attempts to answer these questions through the three objectives which are to identify the applications of integrating AI with BIM in construction projects, to determine the barriers of adopting AI with BIM in construction project and to profile the perception of the construction industry towards the integration of AI and BIM in construction projects. The development of the study and major findings are summarised in the theoretical framework. The applications identified in this study include generative design, construction simulation, 3D coordination and clash detection, automated cost estimation and automated site progress monitoring. The mixed mode method is adopted for this study to gather both quantitative and qualitative data. A total of 145 questionnaire responses were collected and three interviewees were interviewed. The findings revealed that construction practitioners are vastly interested in this integration and they are willing to try this technology. Nonetheless, the high cost of investing in advanced software with AI had led them to think twice about this implementation. Besides, construction practitioners are still slowly shifting from traditional 2D CAD software to BIM adoption. These findings are valuable for the development of BIM automation in construction. Future studies are recommended to develop a detailed prototype for the integration of BIM and AI.